ANALISIS TERHADAP STRATEGI MENINGKATKAN KECERDASAN LINGUISTIK SISWA SEKOLAH DASAR - Hariyanto, Hariyanto; Ardiansyah, Ardiansyah; Mahmud, Salami (Yayasan An-Nur Meunara Baro, 2025)
The development of linguistic abilities in elementary school students is very important, this is because students' linguistic abilities have an influence on students' readiness to take part in learning at a higher level. This research uses a qualitative descriptive research method with literature study (library research). Literature study (library study) is research by collecting data through reading, literature, books, or several other references related to the problem being studied. This research using literature studies utilizes readings related to the research. The research subjects in this study were elementary school students. Based on the research results found, it shows that the theory of multiple intelligences initiated by experts, one of whom is Gardner, reveals the number (plural) of intelligence possessed by each individual. Apart from that, strategies to improve one of the multiple intelligences, namely linguistic intelligence, in elementary school children generally have several methods, here are 5 methods: singing method, field trip method, talking science method, interactive animation-based method, and storytelling method. These five methods are said to be able to train students in improving children's abilities in linguistic intelligence, also through activities that support students' linguistic abilities to be directed in channeling them.